Perlindungan Hukum terhadap Profesi Ners yang Berpraktik Keperawatan Mandiri Berdasarkan Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Titik Sugianti (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
The practice of independent nursing by nurses is a form of professional health services that require assurance of certainty and legal protection, especially after the enactment of Law Number 17 of 2023 concerning Health (Health Law) which integrates various health regulations. This study aims to analyze the form of legal protection for nurses in independent practice and identify the supporting and inhibiting factors for this legal protection. Problem formulation, 1) What is the form of legal protection for nurses who provide independent nursing practice services, 2) What are the supporting and inhibiting factors for legal protection for nurses who provide independent nursing practice. The research method used is normative legal research with a qualitative approach, sourced from secondary data in the form of laws and regulations and related legal literature. The results of the study show that the form of legal protection for nurses includes legality guarantees through STR and SIPP, compliance with professional standards and SPO, and the function of medical records as authentic evidence. The main supporting factors include the existence of a clear legal umbrella and nurses' compliance with regulations, while the inhibiting factors involve illegal practices (without permission), negligence in documentation, and ambiguity of authority. Conclusion: Legal protection for Nurse Practitioners in independent nursing practice is conditional and highly dependent on nurses' compliance with applicable legal norms and professional standards. Compliance with licensing, practice standards, and accurate documentation is the main key in optimizing the guarantee of legal protection.